The Analysis of Academic Community Satisfaction with Public Services in The Higher Education Service Institution - Bambang Santoso Haryono; Muhammad Adie Karya; Sujarwoto Sujarwoto (STKIP Singkawang, 2024)
The services quality will provide a satisfied perception of the services provided by the government. Public services provided by the government are felt to have not met the expectations of the community, as evidenced by the complaints submitted by the service users. This study aims to analyze the value of the service user satisfaction index on The Higher Education Service Institution (LLDIKTI) Region XI services in an effort to determine and evaluate the dimensions of the service quality. The descriptive quantitative is used as the research method. In this research, the data collection techniques using questionnaires, observation as primary data, and literature study as secondary data. The data analysis technique is guided by Permenpanrb number 14 of 2017. The results, 1) The service user satisfaction index obtained a value of 87.13, which means that the perception of satisfaction with the quality of LLDIKTI Region XI services is considered GOOD. However, it is still below based on the Ministry of Education and Culture's road map targets of 92.0. 2) In the ServQual dimension with indicators of Tangibles (U9), Reliability (U1, U2, U5), Assurance (U6), Empathy (U7), Responsiveness (U3) are below the value of 92.0. 3) There is no policy specifically to regulate the follow-up of public satisfaction survey results. 4) The digital services in the services that are dominantly accessed by service users, namely resource services, and PDDIKTI services. So, further research is needed to find out the factors that affect the quality of digital services on the service user satisfaction.